PEMANFAATAN KULIT KAYU GEMOR (Alseodaphne sp.) DAN CANGKANG KEMIRI (Aleurites molucca) UNTUK OBAT NYAMUK ALAMI - Budi Tri Cahyana; Andri Taruna Rachmadi (Jurnal Riset Industri Hasil Hutan, 2011)
Blood fever and Chikungunya cases in Indonesia are increasing annually. For preventing the mosquios, people use mosquito coil which is contain dangerous chemical compound. This research has successly created a natural mosquito coil with gemor bark and hazelnut fruit shell as the main material. Gemor bark is positive containing alcaloid,tanin, phenolk, flvonoid, triterpnoid and glycocydic compounds which are natural bioinsecticide. As formulation the comparison of gemor bark and hazelnut shell as follow :100% : 0 %  ; 80 % : 20 % ; 65 % : 35 % ; 50 % : 50 % ; 35 % : 65% and 20 % : 80% were used. Base one random variance analysis, the best formula was the using of gemor bark in 50%, 35% and  20% of concentration. The mosquitos killing force analysis was using the LT50 for 6 days with 5 diferent concentrations. The result showed that 50 %  of gemor bark was significantly influenced in the killing force. From the economic view, the producion of this coil was cheaper then the same product in the maket. Base on all the result, the research product is applicable in mass producion and safe for human health and the environment.Keywords: gemor bark , hazelnut fruit shell ,  mosquito coil, natural ,  ecofriendly